An investigation into dynamic TLPs for smartphone communication: To facilitate timed response in way finding for vision impaired people - De Silva, D.; Murray, Iain (IEEE Computer Society, 2013)
A reliable, high speed and efficient data transfer method is a very important factor in real time Way-finding systems since it requires information with very low latency to discover paths, avoid dangerous situations, identified changes in existing maps and alternative routes. This research will develop models and methods to facilitate bounded timing with minimal latency for way-finding application for vision impaired people. As a result of analyzing the requirements for Way-finding applications, it was noted that some typical behaviours involve relatively small amount of data transfer through networks. Existing Transport Layer Protocols (TLP) are not ideal for providing such requirements. This research investigates existing TLPs and proposes modifications / extensions to facilitate demands in Way-finding applications and will implement the Dynamic TLP to incorporate both reliable data transfers with high efficiency as well as frequent data transfers which do not require reliability.